The Influence of Social Media in Developing UMKM Enterprises (Small and Medium Micro Enterprises) in Tanjung Raya District, Agam District - Rahmadani, Fauza; S, Siska Febriyanti (Rangkiang: Journal of Islamic Economics and Business, 2024)
The main problem in this study is the number of SMEs that are active in District of Tanjung Raya as many as 150 SMEs. In Tanjung Raya District there are various types of businessess such as typical Maninjau food, drinks, chips, patstries and so on. In this business, many MSME actors. To face this competition, there are several MSME business actors sell the same product and in the same location, resulting in competition between MSME actors. To face this competition, there are several MSME business actors who use social media to promote or introduce their products. Of the 150 active MSMEs, only 40 MSMEs use social media. The purpose of this study was to determine the use of social media in developing MSME businessess in Tanjung Raya. The type of research that the authors conducted was field research with qualitative methods to obtain data form the problems studied. Data collection techniques that the authors use are observation, interviews and documentation. The results of this study are thatdevelopment of MSME businesses that have used social media has in increased compared to before using social media. The social media used for promotion are Facebook, Instagram, WhatsApp. Promotion carried out by MSME business actors is to display photos and videos about the products being sold. It can be concluded that this social media really helps MSMEs in increasing income and having regular customers.